Environmental Movements in North-East India: Political Opportunity Structure and Movement Success. Issue 2 (December 2021) - Rout, Satyapriya; Yudik, Annu
Since the last two decades, the North-East region of India witnessed many environmental movements with similar goals and forms of mobilisation that challenged government policies and actions. Many of them achieved their goals or objectives whereas others failed. This study is an attempt to understand the factors that determined the success and failure of those movements and protests by employing rich details of four case studies from the North-East to make a systematic comparison. This study uses political opportunity structure as a theoretical construct to understand relative success and failure of environmental movements in the North-East.